Analisis Regresi Linear Berganda dalam Menentukan Pengaruh Kinerja Keuangan terhadap Harga Saham Perusahaan LQ-45 di Bursa Efek Indonesia - Khatimah, Havifah Husnatul; Helma, Helma (Journal of Mathematics UNP, 2024)
The stock price is the value formed by the negotiation between sellers and buyers on the stock exchange. Uncertainty in forecasting stock prices is a problem for investors because stock prices are always fluctuating. One of the internal factors affecting stock prices is financial performance. The aim of this research is to create a multiple linear regression model of the factors influencing stock prices and to identify the factors that significantly affect stock prices in LQ-45 companies on the Indonesia Stock Exchange. The analysis used is multiple linear regression analysis. The multiple linear regression model that describes the factors influencing stock prices in LQ-45 companies on the Indonesia Stock Exchange is: ???? = 7.391 + 0.01004 ????1+ 0.000901 ????2 + 0.01351 ????4.Based on the research, it was found that the factors significantly affecting stock prices in LQ-45 companies on the Indonesia Stock Exchange are Price to Earnings Ratio (x1), Earnings per Share (x2 ), and Return on Equity (x4 ) with an error rate of 5%.Keywords: Multiple Linear Regression, Stock Price, Financial Performance